PENERAPAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN PADA KANTOR AKUNTAN PUBLIK BAMS - Muhammad Raihan Renova (2022)
This study aims to determine changes in the payroll accounting system at the BAMS Public Accounting Firm after being affected by the Covid-19 Pandemic. The object of this research is the BAMS Public Accounting Firm. This study uses the interview method directly to the resource person, namely the Senior Auditor at the BAMS Public Accounting Firm with the validity of the data according to the results of the interview. The results of this study can be concluded that the BAMS Public Accounting Firm's payroll system has a simple payroll system, after being affected by the Covid-19 Pandemic, the BAMS Public Accounting Firm underwent a slight change in the payroll system. This Final Project has several limitations related to the data provided by the BAMS Public Accountant Office, such as the employee salary list, salary distribution and physical evidence of client decline experienced by the BAMS Public Accounting Firm, because the data is confidential.